Второй раз в первый класс: [роман] / Маша Трауб - Трауб Маша (Проза Маши Трауб, 2017)
Экземпляры: (20180405) / Инвентарный номер: 40287 / Цена: 249.90; 282.60;228.90 / Сис.шифр: Р2 / Авт.знак: Т 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6